Endoscopic approaches to treatment of achalasia - Stavropoulos, Stavros N. (SAGE Publications, 2013)
Endoscopic therapy for achalasia is directed at disrupting or weakening the lower esophageal sphincter (LES). The two most commonly utilized endoscopic interventions are large balloon pneumatic dilation (PD) and botulinum toxin injection (BTI). These interventions have been extensively scrutinized and compared with each other as well as with surgical disruption (myotomy) of the LES. PD is generally more effective in improving dysphagia in achalasia than BTI, with the latter reserved for infirm older people, and PD may approach treatment results attained with myotomy. However, PD may need to be repeated. Small balloon dilation and endoscopic stent placement for achalasia have only been used in select centers. Per oral endoscopic myotomy is a newer endoscopic modality that will likely change the treatment paradigm for achalasia. It arose from the field of natural orifice transluminal endoscopic surgery and represents a scarless endoscopic approach to Heller myotomy. This is a technique that requires extensive training and preparation and thus there should be rigorous accreditation and monitoring of outcomes to ensure safety and efficacy.